2020
DOI: 10.1001/jamanetworkopen.2020.11055
|View full text |Cite
|
Sign up to set email alerts
|

Association of Direct-Acting Antiviral Treatment With Mortality Among Medicare Beneficiaries With Hepatitis C

Abstract: IMPORTANCE Direct-acting antiviral (DAA) drugs are highly effective in curing hepatitis C virus (HCV) infection. Previous simulations showed extended life as a key health advantage of DAA drugs, but real-world evidence on the association between DAA treatment and reduced mortality is limited. OBJECTIVES To examine the association of DAA treatment with mortality among Medicare beneficiaries with hepatitis C. DESIGN, SETTING, AND PARTICIPANTS This cohort study used Medicare claims data of beneficiaries who sough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 45 publications
2
43
0
Order By: Relevance
“…Few studies have assessed the effect of DAAs compared to notreatment and SVR compared to no-SVR on all-cause and liverrelated mortality. 17,18,[29][30][31] Design and comparison groups differ across studies. Our findings on the impact of SVR from DAAs on all-cause and liver-related mortality are consistent with some studies, while a relatively lower reduction was reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have assessed the effect of DAAs compared to notreatment and SVR compared to no-SVR on all-cause and liverrelated mortality. 17,18,[29][30][31] Design and comparison groups differ across studies. Our findings on the impact of SVR from DAAs on all-cause and liver-related mortality are consistent with some studies, while a relatively lower reduction was reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…18 Similar findings of lower all-cause mortality reduction have been reported from Medicare beneficiaries from the US (without cirrhosis aHR 0.51; 95% CI 0.46-0.57). 31 None of these studies assessed the impact of treatment and SVR on drug-related mortality, which is a critical issue among people with HCV in Canada, the US and many other countries. [10][11][12] Overall, our findings indicate a significant impact of DAAs on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recently developed secondgeneration direct-acting antiviral (DAA) drugs have cure rates greater than 90%, which is higher than the 50% cure rate with former interferon-based treatments. 3 In addition, DAAs are easy to administer (1 pill per day), require a short treatment period (8-12 weeks), and have few adverse effects. Direct-acting antiviral therapy is associated with a 49% to 68% reduction in HCV all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Direct-acting antiviral therapy is associated with a 49% to 68% reduction in HCV all-cause mortality. 3,4 The availability of DAAs has therefore given hope that HCV infection can be eliminated. 5 The World Health Organization has set a goal of reducing the incidence of HCV infection by 80% by 2030 and has recommended treating all adults with chronic HCV infection with DAAs.…”
Section: Introductionmentioning
confidence: 99%
“…These two medications had limited efficacy and numerous side effects; a systematic review and meta-analysis estimated that only 25% of patients with chronic HCV infection were treated with these therapies [ 9 ]. The cure rate associated with DAAs is approximately 98% [ 10 ], which is much higher than the 50% cure rate associated with interferon-based therapy [ 11 ]. Now that the potency of HCV treatment has improved, the focus has shifted to expanding access to treatment and decreasing HCV-associated morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%